2019
DOI: 10.1177/0956462418817050
|View full text |Cite
|
Sign up to set email alerts
|

Female sex workers in Kigali, Rwanda: a key population at risk of HIV, sexually transmitted infections, and unplanned pregnancy

Abstract: Female sex workers (FSWs) were recruited from known hotspots in Kigali, Rwanda, and offered free, anonymous human immunodeficiency virus (HIV) counseling and testing, diagnosis and treatment of sexually transmitted infections (STIs) and long-acting reversible contraception (LARC). From September 2012 to March 2015, 1168 FSWs sought services, including 587 (50%) who were HIV-positive. More than 90% had previously tested for HIV, and 26% who reported previously testing negative had seroconverted. Of the 349 who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 55 publications
(57 reference statements)
4
23
0
Order By: Relevance
“…Our finding that nearly all FSW (95%) reported ever testing for HIV test is higher than the proportion (55%) previously reported in this setting [6], but consistent with findings from Kenya, Benin and Rwanda, where 86.6%, 87.1% and 90.0% of FSW, respectively, reported ever testing for HIV [28,34,35]. The higher testing rates we found could be due to targeted HIV testing programs for FSW in Uganda which aim to achieve the national strategic plan target of at least 90% testing coverage among persons with HIV in order to achieve HIV epidemic control by 2030 [19,36].…”
Section: Discussionsupporting
confidence: 90%
“…Our finding that nearly all FSW (95%) reported ever testing for HIV test is higher than the proportion (55%) previously reported in this setting [6], but consistent with findings from Kenya, Benin and Rwanda, where 86.6%, 87.1% and 90.0% of FSW, respectively, reported ever testing for HIV [28,34,35]. The higher testing rates we found could be due to targeted HIV testing programs for FSW in Uganda which aim to achieve the national strategic plan target of at least 90% testing coverage among persons with HIV in order to achieve HIV epidemic control by 2030 [19,36].…”
Section: Discussionsupporting
confidence: 90%
“…The design of this study was informed by findings of formative, qualitative research conducted with patients at study health centres, 15 clinical experiences of several of the authors, along with input from public health and clinical leaders in Rwanda. The research questions and design were reviewed by investigators with expertise in HIV health service delivery and infectious diseases, along with input from an advisory committee consisting of leadership from study health centres as well as the Rwanda Biomedical Centre, the nation’s central health implementation agency.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier research in Rwanda identified frequent appointments as burdensome to newly diagnosed PLHIV because of structural issues such as transportation cost and long wait times, as well as stigma experienced while travelling to and while at the health centre. 15 Modifying the definition of clinically stable adults living with HIV to decrease the time on ART and reduce the number of viral load measurements could potentially reduce the burden faced by patients and health systems. However, implementing DSD earlier in patients’ treatment may not provide them with the support needed to become stable in care and achieve viral suppression.…”
Section: Introductionmentioning
confidence: 99%
“…It was not defined explicitly and held unstable meaning, even within the same document. These ambiguities have proven persistent [5‐10] (See Appendix ).…”
Section: Discussionmentioning
confidence: 99%